Redesigning The Organization Of The Jakarta City Government: Adaptation And Innovation Towards A Sustainable City - Munjirin Munjirin (Eduvest - Journal of Universal Studies, 2024)
The challenges faced by the Provincial Government of DKI Jakarta in dealing with its change in status as the special capital region have triggered the need for a comprehensive evaluation of the existing spatial and governance systems. Discussions between the Acting Governor of DKI Jakarta and the Minister of National Development Planning indicate the importance of collaboration between central and regional government institutions in ensuring effective adaptation. In the context of relocating the national capital to East Kalimantan, Jakarta is confronted with the challenge of restructuring its government organization to manage environmental challenges, enhance the quality of public services, and ensure development sustainability. The primary focus of the Jakarta Government is on economic development and recovery, which requires restructuring the government organization to enhance the quality of public services and adapt to digital transformation. Redesigning the government organization is essential to ensure smooth transition and sustainable development in the future. Gap analysis shows that Jakarta faces several issues in organizational structure, workflow processes, human resources, and information technology. This research utilizes a qualitative approach with a case study method, collecting data from various sources, including literature reviews and official documents such as laws and regulations, as well as Government performance reports. It is hoped that the findings of this research will provide a comprehensive overview of the changes in the government organization in Jakarta City and offer valuable insights to the local government in their efforts to improve performance and effectiveness, as well as ensure development sustainability in the future.